Gender, airborne chemical monitoring, and physical work environment are related to indoor air symptoms among nonindustrial workers in the Klang Valley, Malaysia - Syazwan AI; Hafizan J; Baharudin MR; Azman AZF; Izwyn Z; Zulfadhli I; Syahidatussyakirah K (Dove Medical Press, 2013)
Aizat Ismail Syazwan,1 Juahir Hafizan,2 Mohd Rafee Baharudin,1 Ahmad Zaid Fattah Azman,1 Zulkapri Izwyn,3 Ismail Zulfadhli,4 Katis Syahidatussyakirah11Department of Community Health, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia; 2Department of Environmental Science/Environmental Forensics Research Center (ENFORCE), Universiti Putra Malaysia, Selangor, 3Department of Biosciences and Health Science, Universiti Teknologi Malaysia; 4Faculty of Built Environment, Universiti Teknologi Malaysia, Johor, MalaysiaObjectives: The purpose of this study was to analyze the relationship of airborne chemicals and the physical work environment risk element on the indoor air symptoms of nonindustrial workers.Design: A cross-sectional study consisting of 200 office workers. A random selection of 200 buildings was analyzed for exposure and indoor air symptoms based on a pilot study in the Klang Valley, Malaysia.Methods: A set of modified published questionnaires by the Department of Occupational Safety and Health (DOSH), Malaysia and a previous study (MM040NA questionnaire) pertaining to indoor air symptoms was used in the evaluation process of the indoor air symptoms. Statistical analyses involving logistic regression and linear regression were used to determine the relationship between exposure and indoor air symptoms for use in the development of an indoor risk matrix.Results: The results indicate that some indoor air pollutants (carbon monoxide, formaldehyde, total volatile organic compound, and dust) are related to indoor air symptoms of men and women. Temperature and relative humidity showed a positive association with complaints related to the perceived indoor environmental condition (drafts and inconsistency of temperature). Men predominantly reported general symptoms when stratification of gender involved exposure to formaldehyde. Women reported high levels of complaints related to mucosal and general symptoms from exposure to the dust level indoors.Conclusion: Exposure to pollutants (total volatile organic compounds, carbon monoxide, and formaldehyde) and physical stressors (air temperature and relative humidity) influence reported symptoms of office workers. These parameters should be focused upon and graded as one of the important elements in the grading procedure when qualitatively evaluating the indoor environment.Keywords: sick building syndrome (SBS), regression analysis, environmental climate factor, occupational exposure, asthma, allergy